2010
DOI: 10.1080/02699930802618918
|View full text |Cite
|
Sign up to set email alerts
|

Impact of individual differences upon emotion-induced memory trade-offs

Abstract: After seeing a scene containing an emotional component (e.g., a snake in a forest) people often demonstrate a "trade-off" in memory, where memory for the emotional component (e.g., the snake) is good, but memory for the nonemotional elements (e.g., the forest) is poor. The result is an incomplete memory retaining central emotional information at the expense of neutral background information. Though almost everyone demonstrates the trade-off, there may be individual differences in the magnitude of the effect. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 62 publications
0
32
0
Order By: Relevance
“…For instance, results from the field of eyewitness memory research show that the central aspects of an emotional scene tend to be better remembered, whereas memory for more peripheral aspects of the scene are poorer compared to neutral scenes (Christianson, 1992;Easterbrook, 1959). However, it has to be noted that recent research indicates that the effects of emotion on item-context tradeoffs are complex and can vary according to multiple factors (Waring et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…For instance, results from the field of eyewitness memory research show that the central aspects of an emotional scene tend to be better remembered, whereas memory for more peripheral aspects of the scene are poorer compared to neutral scenes (Christianson, 1992;Easterbrook, 1959). However, it has to be noted that recent research indicates that the effects of emotion on item-context tradeoffs are complex and can vary according to multiple factors (Waring et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, quite a number of studies using emotional faces, pictures, or sentences have found no modulation of to-be-remembered neutral content (Johansson et al, 2004;Maratos, Dolan, Morris, Henson & Rugg 2001;Righi et al, 2012;Schmidt, 2012;Wiswede, Rüsseler, Hasselbach & Münte 2006). Additionally, there is evidence that enhanced memory for emotional elements in a visual scene may come at the cost of impoverished memory for neutral elements (Kensinger, Piguet, Krendl & Corkin 2005;Waring, Payne, Schacter & Kensinger 2010).…”
Section: Emotional Retrievalmentioning
confidence: 99%
“…1). The stimulus set included items and backgrounds used in prior studies (Kensinger, Gutchess, & Schacter, 2007a, b;Waring & Kensinger, 2009;Waring, Payne, Schacter, & Kensinger, 2010). Care was taken to make sure that the positive, negative, and neutral items were of comparable size and were balanced by approximate scene location.…”
Section: Methodsmentioning
confidence: 99%